Clinical management of an outbreak of Babesiosis in a herd of cattle: a case report - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Osman, Abdinasir Yusuf; Haron, Abdul Wahid; Saharee, Abdul Aziz (International Organization of Scientific Research, 2013)
Eight Friesian-Sahiwal cattle aged between 8 months and 1 ½ years old of both sexes weighing between 100 and 170 kg were infected. The cattle were managed semi intensively. Two weeks before presentation to the University Veterinary Hospital, Universiti Putra Malaysia, two calves died out of 10. The 8 remaining cattle were presented with chief clinical signs of pale mucous membrane, jaundice, and increased respiratory rate, and were diagnosed with Babesiosis. Diagnostic work up was carried out by taking venipuncture blood sample from the cattle and sent to the Clinical Pathology Laboratory for complete blood count (CBC) and biochemistry. Blood sample was also sent to Parasitology Laboratory for blood protozoa evaluation. Ticks were also collected and sent to Parasitology Laboratory for the identification of parasites. Berenil® 5% (Diminazene Aceturate) injection was administered intramuscularly and Ivermectin pour on was applied topically against the blood parasites and for both endo and ecto parasites. The most significant features of the disease are the persistent and consistent lymphocytosis and monocytosis that proves suggestive of the disease from the blood picture and the disease is also associated with muscle degenerations and severe pains and these are additional signs to be observed during the diagnosis of Babesiosis.